Approximately inner derivations - Bratteli, Ola; Kishimoto, Akitaka; Robinson, Derek W. (MATHEMATICA SCANDINAVICA, 2008)
Let α be an approximately inner flow on a C^*-algebra A with generator δ and let δ_n denote the bounded generators of the approximating flows α^(n). We analyze the structure of the set 26739 D={xD(δ): _n→∞δ_n(x)=δ(x)} 26739 of pointwise convergence of the generators. In particular we examine the relationship of D and various cores related to spectral subspaces.